Comparison of Charlson Comorbidity Index and Modified 5-Factor Frailty Index as Clinical Risk Stratification Tools in Predicting Adverse Outcomes in Patients Undergoing Lower Extremity Free-Flap Reconstruction - Huffman, Samuel S.; Bovill, John D.; Deldar, Romina; Gupta, Nisha; Truong, Brian N.; Haffner, Zoë K.; Sayyed, Adaah A.; Fan, Kenneth L.; Evans, Karen K. (Journal of Reconstructive Microsurgery, 2022)
Background Free tissue transfer (FTT) reconstruction is associated with a high rate of limb salvage in patients with chronic lower extremity (LE) wounds. Studies have shown perioperative risk stratification tools (e.g., 5-factor modified frailty index [mFI-5] and Charlson comorbidity index [CCI]) to be useful in predicting adverse outcomes; however, no studies have compared them in patients undergoing LE reconstruction. The aim of this study is to compare the utility of mFI-5 and CCI in predicting postoperative morbidity in elderly patients receiving LE FTT reconstruction.Methods A retrospective review of patients aged 60 years or older who underwent LE FTT reconstruction from 2011 to 2022 was performed. Comorbidity burden was measured by two validated risk-stratification tools: mFI-5 and CCI. Primary outcomes included prolonged postoperative length of stay (LOS), defined as greater than 75th percentile of the cohort, postoperative complications, and eventual amputation.Results A total of 115 patients were identified. Median CCI and mFI-5 were 5 (interquartile range [IQR]: 4–6) and 2 (IQR: 1–3), respectively. Average postoperative LOS was 16.4 days. Twenty-nine patients (25.2%) experienced a postoperative complication, and eight patients (7%) required LE amputation at a mean follow-up of 19.8 months. Overall, flap success was 96.5% (n = 111), and limb salvage rate was 93% (n = 108). Increased CCI was found to be independently predictive of only eventual amputation (odds ratio: 1.59; p = 0.039), while mFI-5 was not predictive of prolonged postoperative LOS, flap complications, or eventual amputation.Conclusion This is the first study to compare the utility of mFI-5 and CCI in predicting adverse outcomes in elderly patients undergoing LE FTT reconstruction. Our results demonstrate CCI to be a superior predictor of secondary amputation in this patient population and mFI-5 to have limited utility. Further investigation in a prospective multicenter cohort is warranted.
Keywords: free tissue transfer; lower extremity reconstruction; risk stratification